A review of the aspects for nutrition and feeding assessment in dairy cattle herd health programs I: herd assessment - Alpízar Solís, Carlos (2017)
Feeding plays a key role in dairy cows’ performance and is mainly aimed at fulfilling their nutritional requirements, guaranteeing their digestive function and health, and optimizing use of available resources and feed rations, in order to obtain the most optimal feeding benefit-profit ratio. Therefore, feeding practices used should meet one or all of the previous objectives.  The purpose of this review is to indicate the main aspects that should be considered at the very least regarding dairy cattle feeding in veterinary herd health programs for dairy farms and as support to the veterinary’s work. In addition, different managing and medical aspects, especially regarding feeding, are integrated here to motivate veterinarians attending dairy farms to develop and use the best tools and methods for farms.  Aspects that can be measured and evaluated in practice are also described and used as a reference to control feeding, the animals’ nutritional status, ruminal health, performance and ration balancing. Nutrition and feeding aspects mentioned here include feed intake, body condition, energy balance, milk production, nitrogen metabolism and digestive function and health. Finally, it is concluded that feed managing in farms must be supported by an overall analysis of the data obtained through the feeding system assessment, together with other aspects such as production and reproduction; in addition, the entire work crew must be involved in the evaluation of results. Efforts must be directed towards reaching the goals initially proposed for the feeding system.